Kemampuan Mengenal Huruf Anak Usia 5-6 - Windri Kapiso; Rapi Us Djuko; Sri Wahyuningsi Laiya (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2021)
The problem in this study What is the ability of children to recognize letters in group B children to kindergarten Al-Qur’an Uswatun Hassanah Ollot 1, West Bolangitang District, Bolaang Mongondow Utara Regency The purpose of this study was to describe the ability to recognize letters in group B children in kindergarten Al-Qur’an Uswatun Hassanah Ollot 1, West Bolangitang District, Bolaang Mongondow Utara Regency. The method used is descriptive are abservation, documentation and interviews. The results showed that the child’s ability to recognize letters was at a very good development stage with an average of 11.75% Starting to develop an average of 82.35% and not yet developing 5.88% in the study it cant be conclude that the ability to recognize letters in group B children at kidergrten Al-Qur’an Uswatun Hassanah Ollot 1, West Bolangitang District, Bolaang Mongondow Utara Regency is starting to develop.